2019
DOI: 10.1111/een.12826
|View full text |Cite
|
Sign up to set email alerts
|

Ant assemblage composition explains high predation pressure on artificial caterpillars during early night

Abstract: 1. Predator-prey interactions, especially those involving herbivorous insects, are of great importance in maintaining biodiversity. Predation pressure varies temporally in response to prey availability and activity. However, little is known about the patterns and drivers of fluctuations in predation pressure at fine temporal scales.2. Artificial caterpillars (placed on plant leaves at breast height) were used to assess changes in predation pressure across four time intervals of the day in a monsoonal tropical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 58 publications
0
16
0
Order By: Relevance
“…For further research, it may be important that evidence is accumulating which shows that predator functional diversity might be more relevant for herbivore reduction than predator species richness [123]. Moreover, observational studies in forests have started to relate diversity measures beyond species richness to predation (e.g., [124]). As research on functional and phylogenetic diversity is just beginning to thrive [14•], future experimental work will likely clarify whether functional and phylogenetic diversity of trees and predators can consolidate tests of the "enemies" hypothesis.…”
Section: Measure Of Diversitymentioning
confidence: 99%
See 1 more Smart Citation
“…For further research, it may be important that evidence is accumulating which shows that predator functional diversity might be more relevant for herbivore reduction than predator species richness [123]. Moreover, observational studies in forests have started to relate diversity measures beyond species richness to predation (e.g., [124]). As research on functional and phylogenetic diversity is just beginning to thrive [14•], future experimental work will likely clarify whether functional and phylogenetic diversity of trees and predators can consolidate tests of the "enemies" hypothesis.…”
Section: Measure Of Diversitymentioning
confidence: 99%
“…Testing Predation and Herbivore Control Predator abundance or diversity is not necessarily the most suitable surrogate of the "enemies" hypothesis, as it is often unclear whether they translate into higher herbivore control, which would require direct measurements of predation pressure [142]. In recent years, indirect means for assessing predation have become popular, especially by scoring attack marks on artificial caterpillars made from plasticine [82,83,87,124,143]. However, whether or not this method allows inference on true predation pressure is questionable.…”
Section: Research Needsmentioning
confidence: 99%
“…In fact parasitoid wasps show preferences toward certain colors (Michaud & Mackauer, 1994, 1995; Lobdell et al ., 2005; Langley et al ., 2006) and shapes of their prey (Pérez et al ., 2012) but the preference depends on wasp species. Although such preferences in ants have not been reported, ant species composition affects predation pressure on dummy caterpillars (Liu et al ., 2019), suggesting that the effectiveness of caterpillar visual traits may vary depending on the assemblage composition of ant species. Although many arthropod predators generally rely on chemical cues for foraging, our results showed that all arthropod predator groups were more or less affected by caterpillar visual traits and that the attack rates on certain visual traits varied seasonally.…”
Section: Discussionmentioning
confidence: 99%
“…Plant damage in the absence of ants was reported to increase between 0 and 250% on average, with the duration of the ant exclosure (Sam, et al 2022), and productivity of the study site (Rosumek, et al 2009, Sam, et al 2022) having signficant impacts. Ant exclosures are difficult to conduct (Hood, et al 2022, Rosumek, et al 2009) thus bait removal is often considered as a proxy of predation (e.g., Liu, et al 2020, Roslin, et al 2017, Burger, et al 2021). Unfortunately, this method may not accurately measure the realized top-down control and trophic cascade to plants from ants.…”
Section: Introductionmentioning
confidence: 99%